Shodh Prastav Kaise Karen Taiyar. - Denicolo, Pam (SAGE Publications, 2017)
How do I go about writing a research proposal? - How do I maximize my chances of Writing a successful research proposals? - How do I do a literature review? Writing a research proposal is one of the most important tasks facing academics, researchers and postgraduate students. In this accessible, informative and entertaining book, Denicolo and Becker tell you how to develop an effective research proposal to secure funding for your research projects or to gain a place on a research degree programme. The book helps you understand what those reading your proposal are looking for and supports the development of writing skills through practical activities. This book offers down-to-earth advice on: - How best to carry out and structure the literature review - How to develop and phrase research questions and hypotheses - How to handle methods and methodology in your proposal - Crucial issues of planning, strategy and timing. This is a must-have book for anyone seeking to write a successful research proposal.